PSYCHOLOGICAL AND INSTITUTIONAL DETERMINANTS OF ZAKAT PAYMENT INTENTION IN A SHARIA-BASED GOVERNANCE CONTEXT: EVIDENCE FROM LANGSA CITY, INDONESIA - Ihsan, Muhammad; Arianty, Erny (JURNAL INFO ARTHA, 2025)
This study examines the factors influencing the intention to pay zakat through Baitul Mal Langsa City, focusing on attitude, subjective norms, perceived behavioral control, accountability, and institutionalization perception. Grounded in stakeholder theory, the theory of planned behavior (TPB), and institutionalization theory, data were collected through an online questionnaire using a convenience sampling method, yielding 97 respondents who had previously paid zakat through Baitul Mal Langsa City. The data were analyzed using the PLSSEM method. The results show that attitude, perceived behavioral control, and institutionalization perception significantly and positively affect muzaki’s intention to pay zakat through Baitul Mal Langsa City, whereas subjective norms and accountability have no significant impact. These findings highlight the importance of institutional perception in strengthening zakat compliance, especially in regions where zakat payment is regulated by law. The study’s implications suggest that Baitul Mal Langsa City should develop effective socialization strategies, improving accessibility to zakat services, and clarifying controversial aspects of the regional zakat regulation.